Managers' perceptions of mental illness in Barbadian workplaces: an exploratory study. Issue 3 (8th May 2017) - Devonish, Dwayne
Abstract : Purpose: The purpose of this paper is to examine the perceptions of private and public sector managers in Barbados regarding the concepts of mental health and illness at work. It also explored their interactions and experiences with persons with mental illness at work and various forms of support and resources needed to improve the overall management of these persons within the organisational setting. Design/methodology/approach: This qualitative study used an exploratory research design based on two focus groups of private and public sector managers. Findings: The findings revealed that both private and public sector managers understood the distinction between the concepts of mental health and mental illness. However, managers believed that high levels of stigma and discrimination exist in both private and public sector workplaces due to a lack of understanding of mental illness, cultural norms, and socialisation in Barbados regarding mental illness and negative stereotypes. However, workplace education and promotion, associated workplace policies, and employee assistance programmes (EAPs) were identified as key strategies for effectively addressing issues of mental health stigma and the management of persons with mental illness at work. Research limitations/implications: Due to the qualitative approach used and small sample selected based on non-probability sampling, generalising the findings to larger populations is heavily cautioned. Practical implications: Organisations in both private and public sectors should emphasise workplace mental health interventions such as mental health education and awareness, the development and implementation of supportive and flexible policies, and EAPs. These strategies are likely to help destigmatisation efforts and enhance managers' understanding of mental health and the management of persons with mental illness. Originality/value: This study provided a rich and in-depth understanding of mental health and illness from the perspective of private and public sector managers in a small developing country in the Caribbean. The Caribbean region possesses a dearth of empirical research concerning issues of mental health and illness at work.